Open Innovation Capabilities and Competences - Brusila-Meltovaara, Kristiina; Makkonen, Pekka; Siakas, Kerstin; Lampropoulos, Georgios (Universidade Portucalense, 2024)
Productivity can be enhanced and competitive advantages can be gained by using an open innovation approach instead of a closed innovation approach. The successful implementation of an open innovation approach requires careful examination of the existing innovation capabilities and competences of a company. This study aims to explore and give a picture of the current level of open innovation capabilities and competences of companies with particular emphasis on companies in Finland. A quantitative approach was followed and a 13-item survey was administered. The reliability of the survey used was .957 and its items included statements regarding the five-level maturity model for open innovation. Level five of the model represents the highest maturity level and level one of the model corresponds to the lowest. Claims regarding maturity level one were excluded as innovation activities do not occur at this level. The survey was administered in both 2022 and 2024 and consisted of three questions for each maturity level from level two to level four and four questions for level three. Maturity levels four and five indicate that companies understand the significance of strategic thinking and that they also include innovation strategies within their general strategy or perceive it as an integral addition to their strategy. We conclude that the effective open innovation culture forms an essential part of the overall success of a company. Therefore, an increase in innovation culture characteristics simultaneously results in an increase in the innovation maturity level.
Keywords: innovation maturity; innovation competences; open innovation; fi=Tuotantotalous|en=Industrial Management|